Protectionism: This Good Bad Word - Monzon, Gabriel Anibal (European Scientific Journal, ESJ, 2017)
This paper aims to determine the place the economy occupies in sciences and, in turn, the place occupied by Protectionism like school of thought within the economy. From the origin of the stipulated capriciously of the economy as Normative Science, the concentrated economic power has tried in creating awareness among people that Protectionism is harmful. As a result, the only way to development and welfare is Liberalism. This position, convenient for those who are directly benefiting from the accumulation and concentration of wealth, involves the one they have been promoting from the media. It is assumed as an absolute truth and is used for generating the collective consciousness that Liberalism is the only way out. In addition, this is even at the expense of the interests of the people.